Goodnight Desdemona (good morning Juliet) - MacDonald, Ann-Marie 1958- (Vintage Canada, 1998)
In this exuberant comedy - and original revision of Shakespeare's Othello and Romeo and Juliet - Constance Ledbelly, a drab and dusty academic, deciphers a cryptic manuscript she believes to be the original source for the tragedies, and is transported into the plays themselves. She visits Juliet and Desdemona, has a hand in saving them from the deaths the Bard had planned for them, and finds out what these women are all about. In true Shakespearean spirit, Constance plunders the plays and creates something new, all the while engaging in a personal voyage of self-discovery. With an abundance of twists, fights, dances, seductions and wild surprises, the play is an absolute joy in theatricality. - Back Cover.